Interaction between the Mid-Atlantic Ridge and the Azores hot spot during the last 85 Myr: Emplacement and rifting of the hot spot-derived plateaus - Gente, Pascal; Dyment, Jérôme; Maia, Marcia; Goslin, Jean (Geochemistry, Geophysics, Geosystems, 2003)
International audience Multiple- and single-beam bathymetric data are compiled over the Azores plateau to produce a 1 km × 1 km grid between latitudes 32°N and 49°N and longitudes 22°W and 43°W. Mantle Bouguer anomalies are then calculated from this grid and the satellite-derived gravity. These grids provide new insights on the temporal and spatial variations of melt supply to the ridge axis. The elevated seafloor of the Azores plateau is interpreted as resulting from the interaction of a mantle plume with the Mid-Atlantic Ridge (MAR). The presence of a large region of elevated seafloor associated with a thick crust between the Great Meteor Seamounts and the Azores platform on the Africa plate, and less developed conjugate structures on the North America plate, favors genetic relations between these hot spot-derived structures. This suggests that a ridge-hot spot interaction has occurred in this region since 85 Ma. This interaction migrated northward along the ridge axis as a result of the SSE absolute motion of the Africa plate, following a direction grossly parallel to the orientation of the MAR. Kinematic reconstructions from chron 13 (∼35 Ma) to the present allow a proposal that the formation of the Azores plateau began around 20 Ma and ended around 7 Ma. A sharp bathymetric step is associated with the beginning of important melt supply around 20 Ma. The excess of melt production is controlled by the interaction of the ridge and hot spot melting zones. The geometry and distribution of the smaller-scale features on the plateau record episodic variations of the hot spot melt production. The periodicity of these variations is about 3-5 Myr. Following the rapid decrease of widespread volcanism, the plateau was subsequently rifted from north to south by the Mid-Atlantic Ridge since 7 Ma. This rifting begins when the MAR melting zone is progressively shifted away from the 200-km plume thermal anomaly. These results bear important consequences on the motion of the Africa plate relative to the Azores hot spot. ...